2018
DOI: 10.1016/j.chembiol.2018.04.017
|View full text |Cite
|
Sign up to set email alerts
|

PDn-3 DPA Pathway Regulates Human Monocyte Differentiation and Macrophage Function

Abstract: SummaryMacrophages are central in orchestrating the clearance of apoptotic cells and cellular debris during inflammation, with the mechanism(s) regulating this process remaining of interest. Herein, we found that the n-3 docosapentaenoic acid-derived protectin (PDn-3 DPA) biosynthetic pathway regulated the differentiation of human monocytes, altering macrophage phenotype, efferocytosis, and bacterial phagocytosis. Using lipid mediator profiling, human primary cells and recombinant enzymes we found that human 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 44 publications
0
51
0
Order By: Relevance
“…Different macrophage subsets, for example, display distinct lipid mediator profiles with monocyte-derived-macrophages skewed towards a classic phenotype expressing higher amounts of pro-inflammatory eicosanoids, whereas cells with an alternatively activated phenotype display higher concentrations of pro-resolving mediators (2325). This shift is also linked with a differential expression of both lipid mediator biosynthetic enzymes as well as the phosphorylation status of ALOX5 (23, 25, 26). In the present study we found a decrease in the number of leukocytes in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Different macrophage subsets, for example, display distinct lipid mediator profiles with monocyte-derived-macrophages skewed towards a classic phenotype expressing higher amounts of pro-inflammatory eicosanoids, whereas cells with an alternatively activated phenotype display higher concentrations of pro-resolving mediators (2325). This shift is also linked with a differential expression of both lipid mediator biosynthetic enzymes as well as the phosphorylation status of ALOX5 (23, 25, 26). In the present study we found a decrease in the number of leukocytes in the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…34 Partial least square projection to latent structures discriminant analysis (PLS-DA) was performed using SIMCA 14.1 software (Umetrics, Umea, Sweden). Evaluation of loading plots was performed as previously described, 35 and variables with best discriminatory power (variable importance in projection ≥ 1) were highlighted in the Score plot.…”
Section: Cytokine Measurementmentioning
confidence: 99%
“…Many actions exerted by SPMs to limit infection have been described in non-CF cells isolated from human and mice macrophages, ( Chiang et al, 2012 ; Colas et al, 2016 ; Pierdomenico et al, 2017 ; Codagnone et al, 2018 ) ( Table 3 ). In addition, SPMs (PDn-3DPA, RvD1, and RvD2) stimulate macrophage differentiation from a pro-inflammatory (M1) to a pro-resolutive phenotype (M2) in non-CF models ( Dalli and Serhan, 2012 ; Recchiuti et al, 2014 ; Croasdell et al, 2015 ; Pistorius et al, 2018 ) and enhance the expression of surface receptors involved in the uptake of apoptotic cells ( Matte et al, 2019 ) ( Table 3 ). RvD2 also reduces polymicrobial sepsis severity in mice ( Spite et al, 2009 ) and MaR1 and RvD3 enhance E. coli phagocytosis by macrophages ( Colas et al, 2016 ) ( Table 3 ).…”
Section: Impact Of Spm S Demonstrated In Cf Modelsmentioning
confidence: 99%